Penentuan Skala Prioritas Pemeliharaan Jalan Kabupaten di Kabupaten Sambas - Ruskamdi; Widodo, Slamet; Mukti, Elsa Tri (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2024)
Roads and bridges are essential for travel and access to isolated places. To sustain ideal conditions, maintenance must include prevention, care, and repair. Regional autonomy and financial balance between the national and regional governments empower the regency government to manage and use resources. However, funding constraints and inequities in road repair execution in Sambas Regency highlight the need for a more effective priority-setting approach that considers all elements of road maintenance goals. This study will establish the criteria and priority order for road repair in Sambas Regency, West Kalimantan. The research uses the Analytical Hierarchy Process (AHP) technique to identify key criteria such as traffic volume, funding, land use planning, road quality, and policy variables. The study findings show that the financial element is the most important, followed by road quality, traffic volume, policy variables, and land use planning. Furthermore, the Mentibar-Daup road portion has the highest repair priority. The study advises using statistical techniques to choose respondents and ensure that respondents' replies are consistent for more reliable findings.